Inteins as Drug Targets and Therapeutic Tools - Tharappel, Anil Mathew; Li, Zhong; Li, Hongmin (Frontiers in Molecular Biosciences, 2022)
Multidrug-resistant pathogens are of significant concern in recent years. Hence new antifungal and anti-bacterial drug targets are urgently needed before the situation goes beyond control. Inteins are polypeptides that self-splice from exteins without the need for cofactors or external energy, resulting in joining of extein fragments. Inteins are present in many organisms, including human pathogens such as Mycobacterium tuberculosis, Cryptococcus neoformans, C. gattii, and Aspergillus fumigatus. Because intein elements are not present in human genes, they are attractive drug targets to develop antifungals and antibiotics. Thus far, a few inhibitors of intein splicing have been reported. Metal-ions such as Zn2+ and Cu2+, and platinum-containing compound cisplatin inhibit intein splicing in M. tuberculosis and C. neoformans by binding to the active site cysteines. A small-molecule inhibitor 6G-318S and its derivative 6G-319S are found to inhibit intein splicing in C. neoformans and C. gattii with a MIC in nanomolar concentrations. Inteins have also been used in many other applications. Intein can be used in activating a protein inside a cell using small molecules. Moreover, split intein can be used to deliver large genes in experimental gene therapy and to kill selected species in a mixed population of microbes by taking advantage of the toxin-antitoxin system. Furthermore, split inteins are used in synthesizing cyclic peptides and in developing cell culture model to study infectious viruses including SARS-CoV-2 in the biosafety level (BSL) 2 facility. This mini-review discusses the recent research developments of inteins in drug discovery and therapeutic research.